Human rights of women : national and international perspectives - Cook, Rebecca J. (University of Pennsylvania Press, 1994)
How can human rights make a difference in the reality of women's lives? The very notion of human rights implies universal application to both women and men; however, the development of international human rights law has been partial and androcentric, privileging a masculine world view. For most women in the world, reality is long work hours in agriculture or the home, with little or no remuneration, while faced with political and legal processes that ignore their contribution to society and accord little recognition of their particular needs. At the same time, it is a mistake to be limited to a monolithic, essentialized view of women that does not take into account the great differences among women in various regions of the world. For that reason, any attempt to address the human rights of women must consider how they can be protected in the context of their own cultures and traditions. In Human Rights of Women, Rebecca J. Cook and the contributors to this volume seek to analyze how international human rights law applies specifically to women in various cultures worldwide, and to develop strategies to promote equitable application of human rights law at the international, regional, and domestic levels. Their essays present a compelling mixture of reports and case studies from various regions in the world, combined with scholarly assessments of various aspects of international law as these rights specifically apply to women. The book addresses multiple and overlapping agendas: international human rights law, feminist studies, family law, political science, third world studies, jurisprudence, and philosophy. Human Rights of Women gives added inspiration and new opportunities to activists, including but not limited to legal practitioners, who seek practical means by which to make the world fairer for women both inside and outside their homes. A volume in the Pennsylvania Studies in Human Rights.
Keywords: Börngen, ...; Women -- Legal status, laws, etc.; Women's rights.; Human rights.; Feminism.; Women's Rights; Human Rights; Feminism; Femmes -- Droit -- Législation.; Femmes -- Droits.; Droits de l'homme (Droit international); Féminisme.; feminism.; POLITICAL SCIENCE -- Human Rights.; Droits de l'homme (Droit international) .; Mujeres -- Derechos de la mujer.; Derechos civiles.; Feminismo.; Human rights; Women's rights; Menschenrecht; Frau; Mensenrechten.; Vrouwendiscriminatie.; Nationale aspecten.; Internationale aspecten.; Droits de l'homme (droit international); Femmes -- Statut juridique.; Droits de l'homme.; Toronto <1992>